Optimalisasi Edukasi Penggunaan Obat Khusus dan Pemeriksaan Kesehatan di Apotek Aljafni Farma sebagai Upaya Peningkatan Kesehatan Masyarakat Desa Ombulo - Uno, Wiwit Zuriati; Iman, Dian Pratiwi; Lamatenggo, Nina (ABHIPRAYA: Jurnal Pengabdian Masyarakat Kesehatan dan Sains, 2024)
Public health is an important factor in creating prosperity, but there are still many people who do not understand how to use medicine properly and the importance of regular health checks. The aim of this activity is to optimize education on the use of special drugs and health checks at the Aljafni Farma Pharmacy as an effort to improve the quality of health in Ombulo Village, West Limboto District. The method used in this service is a direct outreach approach to the community, as well as simple health checks such as measuring blood pressure, blood sugar and cholesterol. The results of this activity show an increase in public understanding regarding the correct use of medicines and the importance of routine health checks. Apart from that, people are also more aware of the importance of a healthy lifestyle. It is hoped that the continuation of this program will support the creation of a healthier society that is better informed about managing personal health.